Domestic violence and child protection : directions for good practice - Humphreys, Catherine; Stanley, Nicky, 1955- (Jessica Kingsley Publishers, 2006)
How do you respond simultaneously to the needs of adults experiencing domestic violence and the specific needs of their children? Domestic violence and child protection explores the challenges of working effectively in this complex field and offers positive models for practice. Leading practitioners and researchers outline the essential safety considerations for children, adult victims and child protection workers, and stress the importance of children's experiences, using children's own words to describe their diverse needs. The contributors offer examples of good practice in prevention.